Posterior leukoencephalopathy following repair of an ileocecal anastomosis breakdown: a case report and review of the literature - Kasper Ekkehard M; Colen Rivka R; Zinn Pascal O; Chen Clark C (Journal of Medical Case Reports, 2011)
Abstract Introduction Posterior reversible leukoencephalopathy syndrome refers to a constellation of neurologic symptoms related to temporary white matter changes. The disease typically presents in the context of an abrupt and drastic elevation in blood pressure (>180/110 mmHg). We report an unusual case of posterior reversible leukoencephalopathy syndrome in a post-operative setting, with a blood pressure parameter generally tolerated by most patients. Case presentation We report the case of a 22-year-old Caucasian man who suffered acute onset visual acuity loss four days after an ileocecal anastomosis. A head magnetic resonance imaging scan revealed findings typically associated with posterior reversible leukoencephalopathy syndrome. His symptoms developed in the context of blood pressure parameters that are typically well tolerated in a post-operative setting (150-160/80-90 mmHg). He did not have a history of renal failure or immunosuppression. His symptoms resolved with aggressive blood pressure management. Conclusions Posterior reversible leukoencephalopathy syndrome can occur in a post-operative setting with blood pressure parameters typically well-tolerated in most post-surgical patients. Timely diagnosis and treatment will minimize the risk of permanent neurologic injury.